GAMBARAN HASIL SPIROMETRI PADA PASIEN DENGAN GANGGUAN PARU DI INSTALASI REHABILITASI MEDIK RSUP PROF. Dr. R. D. KANDOU MANADO - Lasut, Damiputra V. E.; Marpaung, Elfrida; Sengkey, Lidwina S (FAKULTAS KEDOKTERAN UNSRAT, 2016)
Background: Impaired lung is one of the major causes of morbidity and mortality. Based on etiology, anatomical location, chronic nature of the disease, changes in the structure and functioning of lung disorders can be divided into obstructive pulmonary disorder and restrictive lung disorders. The World Health Organization estimates that by 2020 the prevalence of pulmonary disorders, especially obstructive pulmonary disorder will increase and restrictive lung disorders that continued to show an increase in the incidence in the world. Spirometry is one investigation of pulmonary disorders, which measures the volume of air inhaled and exhaled as well as an investigation to distinguish pulmonary disorders and can be used also for diagnostic purposes, monitoring and prognosis of disease or the severity of pulmonary disorders. Methods: Descriptive study with retrospective approach, namely by collecting data medical records of patients with pulmonary disorders. Conclusion: The number of patients with pulmonary disorder were examined spirometry Installation Medical Rehabilitation Hospital Prof. R. D. Kandou Manado in the period from January to September 2016 are as many as 26 patients. Patients with the most widely based on gender is male as much as 22 cases (84.6%). Based on the most frequent age category is 56-65 years of age by 10 patients (38.5%). Based on the results of spirometry is at most restrictive lung disorders as many as 18 patients (69.2%). and based on the severity of the most severe obstruction that is as much as 7 patients (26.9%). Keywords: Spirometry, Obstructive lung disorders, Restrictive lung Disorders Pendahuluan: Gangguan paru merupakan salah satu penyebab utama morbiditas dan mortalitas. Berdasarkan etiologi, letak anatomis, sifat kronik penyakit, perubahan struktur serta fungsi gangguan paru dibedakan menjadi gangguan paru obstruktif dan gangguan paru restriktif. World Health Organization memperkirakan bahwa menjelang tahun 2020 prevalensi gangguan paru khususnya gangguan paru obstruktif akan meningkat serta gangguan paru restriktif yang terus menunjukan peningkatan angka kejadian di dunia. Spirometri adalah salah satu pemeriksaan penunjang pada gangguan paru yang mengukur volume udara yang dihirup dan dihembuskan serta merupakan pemeriksaan penunjang untuk membedakan gangguan paru dan. Metode: Penelitian deskriptif dengan pendekatan retrospektif yaitu dengan cara mengumpulkan data rekam medik pasien dengan gangguan paru. Kesimpulan: Jumlah pasien dengan gangguan paru di InstalsiRehabilitasi medik RSUP Prof. Dr. R. D Kandou Manado sebanyak 26 pasien. Penderita yang paling banyak berdasarkan jenis kelamin adalah laki-laki sebanyak 22 pasien (84,6%). Berdasarkan kategori usia yang paling sering adalah usia 56-65 tahun sebanyak 10 pasien (38,5%). Berdasarkan hasil pemeriksaan spirometri yang paling banyak adalah gangguan paru restriktif sebanyak 18 pasien (69,2%). dan berdasarkan tingkat keparahannya yang paling banyak yaitu obstruksi sangat berat sebanyak 7 pasien (26,9%). Kata kunci: Spirometri, Gangguan paru obstruktif, Gangguan paru restriktif.